PENGEMBANGAN APLIKASI STANDAR PRODUKSI DAN PEMAKAIAN BAHAN PADA PERUSAHAAN KULIT IMITASI BERBASIS WEBSITE - Muchamad Rusdan; Imam Yunianto; Kurniawan (Jurnal Ilmiah Teknologi Infomasi Terapan (JITTER), 2020)
The purpose of this research is to provide ease in reading articles on the standard production and use of imitation leather. Help reduce the level of errors in viewing the standard article production and use of materials by the operator. Operators can more easily enter and change data on the standard production and use of faux leather. It is helping operators who are elderly and have vision problems in seeing and determining production standards and material usage. Bits of help reduce night shift operator errors that lack concentration when looking at the standard production book and the use of faux leather due to drowsiness. This study uses a qualitative approach to data collection techniques using observation, interviews, and literature study. The system development model used in this study is the Waterfall model. The results of this study indicate that the application of production standards and the use of imitation leather material is very easy to use, fast enough in processing or carrying out its functions, very helpful for operators who have problems with their vision, it is quite feasible to replace the previous production standards.